Effect of feed spacer size and mesh length on permeate flux enhancement driven by forced slip velocity - Foo, Kathleen (2020)
Spiral-wound membrane (SWM) modules have been an important role in industrial desalination and water treatment processes. Concentration polarisation (CP) is a critical problem for membrane processes because prolonged solute accumulation near the membrane surface reduces the membrane performance and promotes fouling. Recent studies have shown that the interactions between forced transient flow and eddy inducers (i.e. spacers) in the SWM modules result in significant permeate flux enhancement and reduction in concentration polarisation. Forced slip velocity is the movement of thin fluid layer adjacent to the membrane surface, which disrupts the concentration boundary layer and promotes mixing in membrane systems. The aim of this thesis is to study the effect of SWM feed spacer geometry on the resonant frequency of forced-slip and the resulting permeate flux enhancement generated by forced-slip perturbation. This thesis uses Computational Fluid Dynamics (CFD) code to simulate and investigate the effect of varying the spacer geometric parameters on the resonant frequency for an unsteady forced-slip, as well as the resulting membrane performance, for a 2D zig-zag spacer. The analysis shows that the resonant frequency is significantly affected by the interaction of the shear layer with successive downstream spacers. The effectiveness of forced-slip reaches a peak (up to 15.6% flux increase) for a spacer size in the range of 0.5<df/hch<0.6 because of the trade-off between mixinginduced forced-slip and the CP modulus. In addition, vortex shedding is suppressed for smaller spacer sizes (df/hch≤0.4), because viscous forces dominate over convective forces due to a smaller filament Reynolds number. As the distance between filaments is increased, the increase in flux due to forced-slip is greater (up to 31.5%), albeit the actual flux decreases because the boundary layer is more developed. These results also reinforce the finding that forced-slip perturbation is more efficient for spacer designs with poor mixing (i.e. high CP).